Multisite clinical evaluation of the iFAST rapid antimicrobial susceptibility test direct from positive blood cultures containing gram-negative organisms - Michael Hornsey; Isobel Taylor; Toby King; Zoe Brown; Daniel Nathan Tomás Cançado; Katie Judd; Eleanor Kuszynski; Rowena Lines; Rhiannon Lyon; Xiang Wang; Allyson Lloyd; Robert Impey; et al. (Journal of Clinical Microbiology, 2026)
ABSTRACT iFAST is a label-free rapid antimicrobial susceptibility test (AST) that delivers qualitative results in under 4 h from a positive blood culture bottle. The technique measures changes in the electrical properties of thousands of individual bacteria following exposure to antibiotics. We report the diagnostic accuracy from the first clinical study of the iFAST one rapid AST system in three different centers according to ISO 20776-2:2021. Compared to the reference laboratory broth microdilution method, categorical agreement was 97.8% and 97.2% for the Enterobacterales and non-fermenting gram-negative species, respectively. iFAST specificity and sensitivity for the Enterobacterales were 98.2% and 96.8%, respectively, and 96.9% and 98.4% for the non-fermenting species, exceeding the acceptance criteria (≥95% sensitivity and specificity). Reproducibility was assessed with 12 isolates across 3 sites, in triplicate, on 3 separate days, with different operators at each site. Agreement was 95.7%. IMPORTANCE Even short delays in the initiation of antimicrobial therapy in patients with bloodstream infections are associated with increased morbidity and mortality. Consequently, current guidelines recommend initiation of empiric antimicrobial therapy within 1 h of presentation. However, empiric broad-spectrum therapy may not always be appropriate and can contribute to the selection of resistant organisms. Antimicrobial susceptibility testing (AST) is therefore critical for antimicrobial stewardship and the timely selection of targeted therapy, but conventional methods typically require 1 to 2 days to generate results. This study evaluated the diagnostic accuracy of iFAST, a new low-cost, label-free rapid AST using 375 Enterobacterales and non-fermenter isolates tested directly from positive blood cultures, according to ISO-20776-2:2021. Compared with broth microdilution, iFAST demonstrated high sensitivity, specificity, and categorical agreement, with a time to result of less than 4 h. These findings support the implementation of iFAST for same-shift AST results.